Common Origin of the Circular-Dichroism Pattern in Angle-Resolved Photoemission Spectroscopy of SrTiO3 and Cu⁢Bi2⁢Se3 - Ishida, Y. (2011)
Circular dichroism in the angular distribution of photoelectrons from SrTiO3:Nb and Cu⁢Bi2⁢Se3 is investigated by 7-eV laser angle-resolved photoemission spectroscopy. In addition to the well-known node that occurs in the circular dichroism pattern when the incidence plane matches the mirror plane of the crystal, we show that another type of node occurs when the mirror plane of the crystal is vertical to the incidence plane and the electronic state is two-dimensional. The flower-shaped circular dichroism patterns in the angular distribution occurring around the Fermi level of SrTiO3:Nb and around the Dirac point of Cu⁢Bi2⁢Se3 are explained on equal footings. We point out that the penetration depth of the topological states of Cu⁢Bi2⁢Se3 depends on momentum.